China’s Shifting Policies towards Sustainability: A Low-carbon Economy and Environmental Protection - Guo, Xiumei; Marinova, Dora; Hong, Jin (Taylor & Francis Online, 2013)
China is currently not only the most populous country on earth, but also the world's largest greenhouse gas (GHG) emitter. As China's population growth continues contributing to the overall global population increase, the country remains a significant player in the global problems related to climate change. The Chinese government, however, has recognized that a low-carbon economy is in the country's long-term economic and social interests and this is now a key part of its national development strategy. This paper examines the evolution of policies for sustainability in China and explores their compositions, functions and operational mechanisms. Some emerging features and trends in China's development model are examined, arguing that they represent a clear shift towards sustainability. Further problems and challenges associated with this change and how they impact on China's policies and strategies are also discussed.